Staging Political Authenticity: Does the Same Strategy Fit All? - Holtz-Bacha, Christina (Polity, 2025)
An authentic performance is considered an essential element in the self-presentation of politicians. With the growing number of women entering the electoral contest, the question arises as towhether female candidates (can) use the samestrategies for an authentic performance and whether these are accepted as such by the media and the electorate. This particularly applies to populist female politicians since the staging of authenticity to demonstrate belonging to the “virtuous people” is inherent in the populist communication style and they have to deal with an environment that promotes strong, masculine leadership. This article argues that authenticity is something different for female than for male candidates as a result of the tension between the expectations of female and male behavior, known as double bind and linked to the juggle between the female gender stereotype and the male connoted leadership model that persists in politics. Against this background, four strategies are identified here that have different implications for the performance of authenticity and, in the case of populist female candidates, are additionally influenced by themasculine character of their parties. The use of motherhood for female self-presentation is also discussed as a quasi-universal strategy. Case studies suggest that women react in different ways to the expectations arising from the double bind in their performance of authenticity. Thus, it can be concluded that the same authenticity strategy does not fit all. Future research should therefore applymore complex models of how authenticity is constructed by political actors and impacted by gende
Keywords: authenticity; gender; double bind; self-presentation; campaigning